The Euro Area Periphery Sovereigns' Fiscal Positions and Unconventional Monetary Policy - Oliver Hülsewig; Johann Scharler (Center for Economic Studies and ifo Institute (CESifo), 2020)
We explore the reaction of the euro area periphery sovereigns' fiscal positions to an unconventional monetary policy shock. We estimate panel vector autoregressive (VAR) models over the period 2010-2018, and identify the shock by imposing sign restrictions. Our results suggest that the sovereigns' fiscal positions improve in response to the economic expansion induced by an expansionary non-standard monetary policy innovation which lowers sovereign CDS spreads. Moreover, we observe that fiscal discipline is maintained rather than undermined.
Keywords: E52; E62; H62; H63; 330; euro area periphery sovereigns; fiscal position; unconventional monetary policy; panel vector autoregressive model